Magnetic warping in topological insulators - Gabriele Naselli; Ali G. Moghaddam; Solange Di Napoli; Verónica Vildosola; Ion Cosma Fulga; Jeroen van den Brink; Jorge I. Facio (Physical Review Research, 2022)
We analyze the electronic structure of topological surface states in the family of magnetic topological insulators MnBi_{2n}Te_{3n+1}. We show that, at natural-cleavage surfaces, the Dirac cone warping changes its symmetry from hexagonal to trigonal at the magnetic ordering temperature. In particular, an energy splitting develops between the surface states of the same band index but opposite surface momenta upon formation of the long-range magnetic order. As a consequence, measurements of such energy splittings constitute a simple protocol to detect the magnetic ordering via the surface electronic structure, alternative to the detection of the surface magnetic gap. Interestingly, while the latter signals a nonzero surface magnetization, the trigonal warping predicted here is, in addition, sensitive to the direction of the surface magnetic flux. Our results may be particularly useful when the Dirac point is buried in the projection of the bulk states, caused by certain terminations of the crystal or in hole-doped systems, since in both situations the surface magnetic gap itself is not accessible in photoemission experiments.